2019
DOI: 10.1002/eji.201847862
|View full text |Cite
|
Sign up to set email alerts
|

High‐dimensional single‐cell proteomics analysis identifies immune checkpoint signatures and therapeutic targets in ulcerative colitis

Abstract: Immune checkpoints are regulators of immune cells and play key roles in the modulation of immune responses. The role of checkpoints in autoimmune disease is poorly understood but likely to be central since checkpoint inhibition during cancer treatment can cause autoimmunity. We generated a high‐dimensional single‐cell proteomics data set from PBMCs of healthy individuals and patients with ulcerative colitis (UC) by mass cytometry, enabling systems‐wide analyses of immune cell frequencies and cell type‐specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Yu et al (16) reported that IL-21 could regulate the proliferation and response of TFH cells in the colitis microenvironment. Sebastian Fuchs et al found that the frequency of CXCR5 + PD1 + TFH cells in peripheral blood was significantly increased in 5-ASA treated UC patients (37). Decreased circulating FoxP3 + CXCR5 + TFR cells and increased FoxP3 − CXCR5 + TFH cells in UC patients were once reported (17), but their study lacked detailed clinical staging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (16) reported that IL-21 could regulate the proliferation and response of TFH cells in the colitis microenvironment. Sebastian Fuchs et al found that the frequency of CXCR5 + PD1 + TFH cells in peripheral blood was significantly increased in 5-ASA treated UC patients (37). Decreased circulating FoxP3 + CXCR5 + TFR cells and increased FoxP3 − CXCR5 + TFH cells in UC patients were once reported (17), but their study lacked detailed clinical staging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation was performed as described previously ( Fuchs et al, 2019 ) with antibodies listed in Table S4 . A Helios mass cytometry instrument (Fluidigm) was used for sample acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…In UC, infiltration of immune cells into the intestinal mucosa could cause chronic inflammation. Some subtle but significant changes in immune cell frequencies and immune checkpoint expression were observed in patients with UC compared to HCs from a high-dimensional single-cell proteomics data by mass cytometry (94). The results also showed the increased expression of TIM-3 and TIGIT on NK cells, increased expression of CD155, PD-L1 and VISTA on monocytes, and decreased expression of TIGIT on CD4 + T cells (94).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 91%
“…NK cells are present in the intestinal mucosa under both the healthy and diseased conditions. Recently, a reduced number of peripheral NK cells was observed in UC patients (94). In UC, infiltration of immune cells into the intestinal mucosa could cause chronic inflammation.…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%